1990
DOI: 10.3354/meps064055
|View full text |Cite
|
Sign up to set email alerts
|

Short-term predation responses of adult bay anchovies Anchoa mitchilli to estuarine zooplankton availability

Abstract: Feeding activity and prey selection of adult bay anchovies Anchoa mitchilli in the highsalinity North Inlet Estuary, South Carollna (USA), were examined during 2 summer days and nights in 1985. Stomach contents were compared to 2 size fractions of zooplankton (153 and 365 pm mesh) collected at the same time (every 2 h) and place (near the bottom) in a tidal creek. Adult bay anchovies (40 to 60 mm) consumed a wide variety of zooplankton, but selected items according to prey size, density, and type. Most prey it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 51 publications
0
23
0
1
Order By: Relevance
“…Castro and Cowen (1991) found no difference in the density of day and night collections of larval A. mitchilli in vegetated areas, suggesting that the presence of vegetation primarily affects juveniles and adults. Anchoa mitchilli is an opportunistic, selective zooplanktivore (Johnson et al 1990) that may be less successful at foraging in dense vegetation. This hypothesis is supported by the fact that anchovies collected in vegetated areas have lower body weights than those collected fromunvegetated areas (Herke 1971).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Castro and Cowen (1991) found no difference in the density of day and night collections of larval A. mitchilli in vegetated areas, suggesting that the presence of vegetation primarily affects juveniles and adults. Anchoa mitchilli is an opportunistic, selective zooplanktivore (Johnson et al 1990) that may be less successful at foraging in dense vegetation. This hypothesis is supported by the fact that anchovies collected in vegetated areas have lower body weights than those collected fromunvegetated areas (Herke 1971).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the fact that anchovies collected in vegetated areas have lower body weights than those collected fromunvegetated areas (Herke 1971). However, A. mitchilli was significantly more abundant in vegetated areas in the daytime, suggesting that it may use dense stands of unbroken vegetation as a refuge from predators (Griffith 1993) and then move out to forage at night ( Johnson et al 1990). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recruiting to marshes during maximum amplitude flood tides also may reduce predation, because megalopae would be transported most quickly and effectively through high densities of fishes to adult habitats. Megalopae do largely appear to avoid predation because an extensive study showed that few of them were eaten by the common planktivorous fishes (anchovies, silversides, killif~shes) inhab~ting Atlantic coast estuaries (Morgan 1990, but see Johnson et al 1990).…”
Section: Feeding Preferences Of Planktivorous Fishesmentioning
confidence: 99%
“…These species are found, often at high density, in intertidal marsh habitats from Cape Cod, Massachusetts to Northern Florida and, for U. pugilator, through the eastern Gulf of Mexico, USA, where they strongly affect energy flow and nutrient cycling (Crane 1975, Montague 1982, Hunter & Feller 1987, Petit & Bildstein 1987, Watts 1988, Johnson et al 1990.…”
Section: Introductionmentioning
confidence: 99%